MARTIAN SUBSURFACE PROPERTIES AND CRATER FORMATION PROCESSES INFERRED FROM FRESH IMPACT CRATER GEOMETRIES - Stewart S.T.; Valiant G.J. (My University, 2006)
The geometry of simple impact craters reflects the properties of the target materials, and the diverse range of fluidized morphologies observed in Martian ejecta blankets are controlled by the near-surface composition and the climate at the time of impact. Using the Mars Orbiter Laser Altimeter (MOLA) data set, quantitative information about the strength of the upper crust and the dynamics of Martian ejecta blankets may be derived from crater geometry measurements. Here, we present the results from geometrical measurements of fresh craters 3-50 km in rim diameter in selected highland (Lunae and Solis Plana) and lowland (Acidalia, Isidis, and Utopia Planitiae) terrains. We find large, resolved differences between the geometrical properties of the freshest highland and lowland craters. Simple lowland craters are 1.5-2.0 times deeper (≥5σo difference) with >50% larger cavities (≥2σo) compared to highland craters of the same diameter. Rim heights and the volume of material above the preimpact surface are slightly greater in the lowlands over most of the size range studied. The different shapes of simple highland and lowland craters indicate that the upper ~6.5 km of the lowland study regions are significantly stronger than the upper crust of the highland plateaus. Lowland craters collapse to final volumes of 45-70% of their transient cavity volumes, while highland craters preserve only 25-50%. The effective yield strength of the upper crust in te lowland regions falls in the range of competent rock, approximately 9-12 MPa, and the highland plateaus may be weaker by a factor of 2 or more, consistent with heavily fractured Noachian layered deposits. The measured volumes of continuous ejecta blankets and uplifted surface materials exceed the predictions from standard crater scaling relationships and Maxwell's Z model of crater excavation by a factor of 3. The excess volume of fluidized ejecta blankets on Mars cannot be explained by concentration of ejecta, through nonballistic emplacement processes and/or bulking. The observations require a modification of the scaling laws and are well fit using a scaling factor of ~1.4 between the transient crater surface diameter to the final crater rim diameter and excavation flow originating from one projectile diameter depth with Z = 2.7. The refined excavation model provides the first observationally constrained set of initial parameters for study of the formation of fluidized ejecta blankets on Mars. © The Meteoritical Society, 2006.